Legal Vacuum Governing the Use of Kirpan for Sikhs Based on Religious Rights and National Constitution - Sukh Dilraj Singh (PT Publikasiku Academic Solution, 2023)
This research raises issues related to the protection of the right to state freedom for Indonesian citizens according to Indonesian national law. Specifically, this research discusses the history of the arrival of the Sikhs and the use of Kirpan in the public space as one of the teachings of the Sikh Religion which is mandatory for Sikhs to follow wherever and whenever. The regulation on the use of Kirpan is still unclear and ambiguous, so there is no legal certainty that protects Sikhs. Sikhs who wish to own and use a Kirpan are required to obtain a permit with the competent authority according to predetermined administrative requirements. However, this only applies to Sikhs who are over 17 years old, while Sikhs who are not yet 17 years old cannot obtain this permit. This has resulted in Sikhs who are under 17 years of age not receiving legal protection in exercising their religious rights. With this legal vacuum, the implementation of human rights in Indonesia is imperfect and not in accordance with Pancasila and the 1945 Constitution of the Republic of Indonesia. This research was conducted using normative juridical methods through literature studies and seeking expert opinion. This study uses a historical approach and a conceptual approach regarding the entry of the Sikh Religion and its teachings. This research is based on primary legal materials in the form of laws and regulations, international regulations, and judge's decisions, as well as secondary legal materials in the form of books, journals, and theses which contain previous research. The legal materials were obtained through library research. The type of analysis used is qualitative, namely by interpreting or interpreting the legal material obtained. The method of interpretation used is the method of grammatical interpretation and the method of historical interpretation. The results of this study state that the Indonesian government must make a law and regulation on the regulation of the use of weapons as a symbol of a religion such as Kirpan without any magical or heritage elements. This is for the sake of implementing religious freedom for Indonesian citizens in Indonesia